The Effectiveness Of Using Hangman Game In The Mastery Of Students’ Vocabulary (International Forum of Researchers and Lecturers, 2023)
This research aims to determine the effectiveness of Hangman game in the mastery of students’ vocabulary in class VII-F of MTsN 9 Jombang. This research used a quantitative method and the research design used is a pre-experimental design. The method used by the researcher was Hangman game. The population of this research is class VII-F of MTsN 9 Jombang consisting of seven classes and the sample taken for this study is class VII-F consisting of 30 students. The researcher conducted the pretest and posttest to find out students’ vocabulary before and after using Hangman game. The result showed that the mean score of the post-test was 79,83 higher than the mean score of the pretest was 51,33. It means that there was an increase in students’ post-test scores. Therefore, the use of Hangman game in the mastery of students’ vocabulary has significant differences in class VII-F of MTsN 9 Jombang.